Making crackers â€œSipandukâ€ from coffee skin as a new breakthrough that has economic value to increase tourism potential - Juliati; Ramadhani, Siti; Musyafa?ah, Anis (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Dedication through the discipline of science as an implementation of the knowledge received in college so that students can answer the challenges of an increasingly rapid era. In the midst of the increasingly strong competition, it is necessary to have a planned, systematic, and applicative activity to train and educate students to become young intellectuals who are qualified and responsive to the problems that arise in the midst of people's lives and are able to look for the solution. Environmental conditions which are plantations, agriculture, and animal husbandry as well as home industries that produce waste that cause many disease sectors that are easily breed and affect the health of livestock and society. The potential, from the extraordinary abundance of coffee from agriculture, has made us take the initiative to make coffee crackers from coffee skins that have been thrown away into waste. With the use of coffee cherry skin, hopefully coffee skin will not become waste. Coffee is not only enjoyed with drinks but can also be made into crackers